Pulmonary histoplasmoma: a disguised malady - Paulo Marcelo Pontes Gomes de Matos; Aloisio Felipe-Silva; José Pinhata Otoch (University of São Paulo, 2019)
Histoplasmosis is a mycosis caused by the dimorphic fungus, Histoplasma capsulatum, which is transmitted via dust and aerosols. Lung involvement is the most common, with a varied clinical presentation. Although it is not the only source of infection, H. capsulatum is frequently found in bat guano, which is the reason why it is highly prevalent among caving practitioners. The solitary histoplasmoma of the lung is an unusual and chronic manifestation of this entity, which mimics, or at least is frequently misconstrued, as a malignancy. Almost invariably, the diagnosis of this type of histoplasmosis presentation is achieved after lung biopsy. The authors present the case of a young woman who sought medical care because of chest pain. The diagnostic work-up revealed the presence of a pulmonary nodule. She was submitted to a thoracotomy and wedge pulmonary resection. The histologic analysis rendered the diagnosis of histoplasmoma. Thisreport aims to call attention to this diagnosis as the differential diagnosis of a pulmonary nodule.